2012
DOI: 10.4161/trns.21810
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary aspects of plastid proteins involved in transcription: The transcription of a tiny genome is mediated by a complicated machinery

Abstract: Chloroplasts in land plants have a small genome consisting of only 100 genes encoding partial sets of proteins for photosynthesis, transcription and translation. Although it has been thought that chloroplast transcription is mediated by a basically cyanobacterium-derived system, due to the endosymbiotic origin of plastids, recent studies suggest the existence of a hybrid transcription machinery containing non-bacterial proteins that have been newly acquired during plant evolution. Here, we highlight chloroplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…PRIN2 is absent from the genomes of green algae and cyanobacteria, indicating that this protein appeared during evolution of the plant lineage and suggesting that it might perform a regulatory function 22 . Analysis of the PRIN2 protein sequences from different plant species showed that the protein lacked putative kinase or phosphatase domains, but revealed the presence of two conserved cysteine residues within the mature protein, Cys68, and Cys115 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PRIN2 is absent from the genomes of green algae and cyanobacteria, indicating that this protein appeared during evolution of the plant lineage and suggesting that it might perform a regulatory function 22 . Analysis of the PRIN2 protein sequences from different plant species showed that the protein lacked putative kinase or phosphatase domains, but revealed the presence of two conserved cysteine residues within the mature protein, Cys68, and Cys115 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The PEP-associated proteins are plant-specific proteins, suggesting that those proteins evolved relatively late compared with the eubacterial core subunits of the PEP complex. Proteins that evolved late in the plant lineage can be linked to regulatory functions coordinating different processes in the cell 22 and could potentially improve the redox regulatory system inherited from cyanobacteria 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Chloroplasts have recruited significant number of eukaryotic proteins from host cells. Thus, chloroplasts possess unique prokaryotic-eukaryotic hybrid systems in several cellular processes, including transcription (Baumgartner et al, 1993 ; Yagi and Shiina, 2011 ), translation and metabolic pathways (Martin and Schnarrenberger, 1997 ; Reyes-Prieto and Bhattacharya, 2007 ; Reyes-Prieto and Moustafa, 2012 ). In total, more than 600 non-cyanobacterial-host-derived proteins contribute to the chloroplast proteome, which includes ~3000 proteins (Abdallah et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…B). Silenced NtEMB2738 blocked chloroplast development in tobacco, and the expression pattern of plastid genes in the silenced tobacco showed a similar pattern to those in PEP‐deficient mutants, such as Δrpos (Hess et al , Allison et al , De Santis‐MacIossek et al , Krause et al , Legen et al ) and ptac mutants (Pfalz et al , , Garcia et al , Myouga et al , Arsova et al , Gao et al , Yagi et al , Yu et al ). These results suggested that EMB2738 was probably involved in the expression of plastid gene in higher plants.…”
Section: Discussionmentioning
confidence: 85%